Status kualitas air untuk penilaian lingkungan sekitar tambak ekstensif di Balikpapan, Kalimantan Timur - Melati, Aulia Firda; Supriyono, Eddy; Hastuti, Yuni Puji; Nirmala, Kukuh (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2024)
The estuary of Salok Api River in Balikpapan City is geographically located right across the Makassar Strait which is a strategic area supporting the economy of the surrounding city. The aquatic environment in any watershed acts as a carrier of various pollutants and affects the water quality in the estuarine area. The main objective of this study is to assess and identify pollutants that flow into the water environment around extensive ponds in Balikpapan City for aquaculture activities. The STORET method was used in this study to determine the water quality status. Water quality data were collected at six different locations around extensive ponds in Balikpapan City in February - March of 2023. A total of 13 water quality parameters (brightness, temperature, TDS, EC, salinity, pH, DO, ammonia, nitrite, nitrate, phosphate, BOD, and COD) were analyzed at six sites to assess the STORET index at each site. The average STORET index at the six sites was (-32, -26, -26, -26, -26, and -38). The results showed that four sites were classified as moderately polluted and the other two sites were classified as heavily polluted. The STORET index at each location is high and the implication is that the area has moderate to poor water quality status due to several parameters such as EC, salinity, pH, DO, ammonia, phosphate, and COD.